HEALTH SYSTEM CHALLENGES IN INDONESIA: EVIDENCE ACROSS FINANCING, ACCESS, AND IMPLEMENTATION - Nur Atika (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2025)
Over the past decade, Indonesia has undergone a major transformation in its health system through the implementation of the National Health Insurance program (Jaminan Kesehatan Nasional or JKN). The program represents one of the largest social health insurance schemes worldwide and reflects the country’s commitment to achieving Universal Health Coverage (UHC). Despite significant progress in expanding coverage, a persistent challenge remains in ensuring equitable access to services, financial protection, and effective implementation of health and social policy. The studies published in this issue provide valuable insight into several interconnected dimensions of Indonesia’s health system, which are health financing, health insurance, service utilization, implementation challenges, and treatment costs. Together, these articles highlight the importance of systemic, data-driven, and equitable reforms in our health system to improve health outcomes. Keywords: Health system, health financing, access, implementation.